Studi Desain Bangunan Pelindung Pantai Tipe Groin Sebagai Upaya Penanganan Abrasi di Pantai Amal Baru Pulau Tarakan - Utomo, Edy; Bakri, Muhammad Djaya (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Borneo Tarakan, 2024)
Amal Baru beach is one of the beaches affected by the erosion phenomenon on Tarakan Island. The phenomenon of abrasion that occurs on this beach is 72% and accretion is 28%, with conditions that change the coastline due to abrasion of 2.59 m/year. The main trigger for the abrasion phenomenon on this beach is the characteristics of the destructive waves that occur on the shoreline. One of the solutions for erosion control is to construct coastal protection structures, such as Groin. In this study, a study was conducted to deal with abrasion problems on the beach by providing alternative Groin structural designs. All data used in this study is secondary data and is representative as data for the design of the Groin structure, which is planned for the next 50 years. The results of the studies conducted provide an alternative number of Groin structures of 5 units with a length of 95 meters and a distance between Groin of 100 meters. The recomended structure is a slooping side building with the main armor layer being tetrapod, with a grain weight of 0.50 tons for the arm structure and 1.00 tons for the structure at the head end of the Groin.